PENGARUH PEMBERIAN JUS NANAS TERHADAP PENURUNAN KADAR KOLESTEROL DI DESA PASAR MERAH TIMUR KOTA MEDAN - HULU, ALFIYAH ANIS; CHANIAGO, LITA SEPTINA (JURNAL ILMIAH MAKSITEK, 2024)
Hypercholesterolemia is one of the lipid metabolism disorders characterized by an increase in total blood cholesterol levels. Hypercholesterolemia is a risk factor for a wide variety of diseases. Cholesterol is a lipophilic molecule that is very important for human life. It has many roles that contribute to normally functioning cells for example, cholesterol is an important component of the cell membrane. Daily consumption of fruits and vegetables is related to blood cholesterol levels, because fruits and vegetables contain fiber that can lower cholesterol levels. The content in pineapple fruit is thought to improve the lipid profile in the blood. Pineapple is a popular tropical fruit that has high nutritional value and medicinal properties. Based on this, researchers want to test the effect of pineapple juice on reducing cholesterol levels in the body, Therefore, pineapple juice can be an alternative to the treatment of hypercholesterolemia. To identify the effect of pineapple juice on the decrease in cholesterol levels. The research design used is a non-equivalent control group design, which is a study conducted with pre and post tests in both groups and followed by interventions in the experimental group. Data analysis results were obtained in the pretest control group with the post test control group (p>0.05) where there was no relationship between the decrease in cholesterol levels in the control group. The pre-test experimental group with the post-test experimental group obtained results (p<0.05) and the value of the post-test control group with the post-test experimental group obtained results (p<0.05) which means that there is a relationship between giving juice to the sample in lowering cholesterol levels. There is an effect of Pineapple fruit juice on reducing lower cholesterol levels.